2016
DOI: 10.3856/vol44-issue1-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Yucca schidigera and Quillaja saponaria on growth performance and enzymes activities of juvenile shrimp Litopenaeus vannamei cultured in low salinity water

Abstract: The inclusion of Yucca schidigera and Quillaja saponaria extracts (NTF) in aquatic organisms display a positive response on production and organism's physiology. Fifteen tanks (140 L) with low-salinity water (S = 5) were stocked with 10 juvenile shrimp (Litopenaeus vannamei, 2.6 g of mean weight) feeding with 0, 0.25, 0.5, 1.0 and 2.0 g kg -1 of NTF of basal diet (triplicate treatment). The shrimp were cultured in a close recirculation system (control condition) and fed ad libitum daily for 40 days. General gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In terms of digestive enzyme activities, no significant differences were found in our results on aminopeptidase, alkaline phosphatase, and lipase from treatments with L0.1% and L0.3% of the inclusion of guishe crude extract in the feed. This fact is consistent with the findings of Hernández‐Acosta et al () when the inclusion between 0% and 0.2% of a mix of extracts of Y. schidigera and Q. saponaria did no affected enzymatic digestive activities in L. vannamei . On this respect, it has been described that dietary protein represents a critical role for shrimp growth (Kureshy & Davis, ; Mente, Coutteau, Houlihan, Davidson, & Sorgeloos, ), and the optimal assimilation and utilization depends mostly on the digestive proteases activities, which in this case the inclusion of L0.6% of the extract in feed reduced the aminopeptidase activity in shrimp, reflected in a lower growth compared with the rest of treatments.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In terms of digestive enzyme activities, no significant differences were found in our results on aminopeptidase, alkaline phosphatase, and lipase from treatments with L0.1% and L0.3% of the inclusion of guishe crude extract in the feed. This fact is consistent with the findings of Hernández‐Acosta et al () when the inclusion between 0% and 0.2% of a mix of extracts of Y. schidigera and Q. saponaria did no affected enzymatic digestive activities in L. vannamei . On this respect, it has been described that dietary protein represents a critical role for shrimp growth (Kureshy & Davis, ; Mente, Coutteau, Houlihan, Davidson, & Sorgeloos, ), and the optimal assimilation and utilization depends mostly on the digestive proteases activities, which in this case the inclusion of L0.6% of the extract in feed reduced the aminopeptidase activity in shrimp, reflected in a lower growth compared with the rest of treatments.…”
Section: Discussionsupporting
confidence: 93%
“…For its part, A. lechuguilla contains 45.34% of compounds with antioxidant properties without specific classification (Carmona, Mussatto, Mussatto, Castillo‐Quiroz, & Ríos‐González, ). Authors have driven the use of this kind of plant in the aquaculture field as Hernández‐Acosta et al (); they demonstrated that the inclusion of Y. schidigera extracts in a commercial diet has a positive effect in the physiology and production of L. vannamei juveniles. In the same manner, Yang et al () reported a significant increase in weight gain of L. vannamei with the inclusion of 0.2% of Y. schidigera extract in the feed, besides an improvement in nonspecific immunity effect and water quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum glucose level was determined using glucose enzymatic PAP by kits obtained from Bio-Merieux, France, according to Trinder (1969). Serum creatinine was determined using the colorimetric method (Heinegård & Tiderström, 1973). At the wavelength of 450 nm using ELISA Microplate Reader, the serum lysozyme activity was assayed (Demers & Bayne, 1997) using clinical kits obtained from Sigma, USA.…”
Section: Serum Biochemical Analysis and Lysozyme Activitymentioning
confidence: 99%